Growth, characterisation and thermal stability of AlN/Ti/AlN/SiO2 multilayer selective solar absorber coating for high temperature applications. (16th July 2022) - Bello, M.; Subramani, S.
In this work, AlN/Ti/AlN/SiO2 multilayer selective solar absorber coating (MSSAC) was deposited onto Fe3 O4 modified stainless steel (SS) substrate using DC/RF magnetron sputtering. The substrate modification was done by simple annealing in air at 600°C for 1 h and achieved rough Fe3 O4 layer on the surface of the substrate. The resulting samples were subjected to heat treatment at various temperatures in air for 2 h, and were characterised by X-ray diffraction, scanning electron microscopy, atomic force microscope, energy dispersive X-ray spectroscopy and UV-Vis-NIR spectrophotometer. The optical constants of the MSSAC were determined from the measured experimental reflectance data. The AlN/Ti/AlN/SiO2 MSSAC was found to be thermally stable up to 500°C in air with high solar absorptance of 93.04 in the solar spectrum range (300-2500 nm) and low thermal emittance of 12.13 in the infrared range (5000-25, 000 nm). However, at 600°C, the solar absorptance decreased to 91.78 from 93.04 and the thermal emittance rose to 19.03 from 12.13, which is attributed to a decrease in the surface roughness of the coatings. This high absorptance is attributed to the interference induced mechanism and the intrinsic properties of the coated materials. These results suggest that AlN/Ti/AlN/SiO2 MSSAC deposited by sputtering onto Fe3 O4 modified SS substrate is a good coating material for high temperature solar absorber applications.